Necesidad de incorporar en la ley de Comunicación, disposiciones que restrinja y Sancione la propaganda de licores, cigarrillos y Otros similares en los diferentes medios Publicitarios - Torres Farías, Gregorio Bernardo (2014)
he daily commercials broadcast by the different is one of the most influential risk factors in establishing habits of drinking and snuff among children, adolescents and young people, in fact, the advertising tactics of companies producing different types of liquor and tobacco that are dedicated to the production and marketing of these products in recent years attracting new consumers, particularly among adolescents and young people, it is about strategic groups for the alcohol and tobacco industry allowing them to expand their potential customer base, while loyalty to ensure these products from an early age. As it is known that some drugs are considered social acceptance and consumption of snuff, beer, these products early experimentation with a high risk starts from the perspective of drug prevention, since there is a high probability that experimental consumption aforementioned substances are repeated and end up as usual, is evident from the moment the existence of high levels of continuity in the consumption of snuff and alcohol, as is evident from the fact that is evidenced by the different media that a considerable number of students who, having spent some time in their life snuff or alcohol repeated use of these substances in the past and are in the process of experiment with other harder drugs such as marijuana (canabais) cocaine base, etc., you could say that the latter months of this year some schools in Guayaquil are under police surveillance in order to prevent and eradicate drug use. From my point of view and some people the consumption of snuff and alcohol use among adolescents is closely related to the multiple strategies launched by tobacco companies and distilleries to promote their use, using beautiful women in little clothing with which draw a lot of attention to the special man in child, adolescent and young, for it invest huge sums of money on advertising and marketing advertising and other strategies to attract customers or potential customers. We are confident that the production, distribution and sale of alcoholic beverages and snuff are in which companies and large multinational corporations vie for leadership of a market with increasing competition prime economic activities. so advertising strategies and advertising content of these products, keep in mind the financial dimension, the maneuverability of these industries, the political and social influence is enormous, the economic activity generated. There are some sectors and companies interested in promoting the sale of these products farmers, winemakers, tobacconists, owners of bars, clubs and restaurants, among which is the advertising industry itself, which depends heavily on the promotion of these products, which to maintain or increase the market share of the tobacco and alcohol industry needs to incorporate every year new consumers of their products, in order to replace those who decide to abandon their use or because they become ill or die. Gender equality dominates right now in Ecuadorian society, the variety of products such as alcohol and snuff, consumption of which satisfies these aspirations, the advertising success lay in converting the consumption of snuff and alcohol catalysts aspirations a generation of young boys and girls, who became synonymous with freedom, transgression, equality or claim an alternative lifestyle, no wonder the advertising has played a key role in strengthening the social imaginary of adolescents and young Ecuadorians on these substances, based on a series of associations that link the consumption of alcohol and snuff with the night, fun, friendship, freedom, social success, independence or pleasure. Some associations, as verifiable later, advertising reinforces repeatedly on your ads that have helped to consolidate a favorable social environment to consumption of these products, which is still a large part of the citizens attributed several positive values that I think this has probably been the most successful advertising of alcohol and snuff, throwing ads for different brands.